Development of Aedes albopictus (Diptera: Culicidae) Larvae Under Different Laboratory Conditions. Issue 1 (14th August 2016) - Puggioli, A.; Carrieri, M.; Dindo, M. L.; Medici, A.; Lees, R. S.; Gilles, J.R.L.; Bellini, R.
Abstract : Critical to successful application of the sterile insect technique against Aedes albopictus (Skuse) is the development of an efficient and standardized rearing protocol to be employed in the mass production system. In this study, several life history traits of Ae. albopictus were analyzed to identify upper and lower thresholds of larval density and diet concentration. Survival to pupation, time to pupation, and sex ratio were evaluated under a range of larval densities (0.5–5 larvae/ml) and food levels (0.05–1.6 mg/larva/d) using two larval diets (one locally developed; one developed by the FAO/IAEA). The larvae reared at 28 °C, at a density of 2 larvae/ml and receiving a food dose equal to 0.6 mg/larva/d of a diet consisting of 50% tuna meal, 50% bovine liver powder (the FAO/IAEA diet), and, as an additive, 0.2 g of Vitamin Mix per 100 ml of diet solution, developed in 5 d and had 90% survival to the pupal stage. With this rearing regime male pupae production 24 h after the onset of pupation was the highest; these pupae were ∼94% male.